TINJAUAN HUKUM EKONOMI SYARIAH TERHADAP PRAKTIK WAKALAH BIL UJRAH ANTAR PEDAGANG PAKAIAN DI PASAR SENTRAL PANGKEP - Algazali, Muhammad; Raehana, Syarifa; Syahid, Akhmad; Lawang, Hasanna; Alwi, Auliah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze the practice of wakalah bil ujrah among clothing traders at Pasar Sentral Pangkep and to examine its compliance from the perspective of Islamic economic law. This research employs a qualitative method with a descriptive and normative-empirical approach. Data were collected through interviews, observations, and documentation, involving clothing traders and the market head as key informants. Data analysis uses the Miles and Huberman model, including data reduction, data display, and conclusion drawing. The results show that the practice of wakalah bil ujrah occurs when a trader who does not have the requested goods seeks them from another trader with the buyer’s approval. In this practice, the intermediary trader acts as an agent (wakil), while the owner of the goods acts as the principal (muwakkil), and the profit is obtained from the price margin. This practice is influenced by the desire to retain customers, limited stock availability, and strong social relationships among traders. It also provides positive impacts such as increasing transaction opportunities and improving distribution efficiency. From the perspective of Islamic economic law, this practice fulfills most of the essential elements of wakalah, including the presence of a principal, an agent, and a clearly defined object, and reflects principles such as mutual assistance, consent, honesty, and fairness. However, it does not fully comply with the requirements of wakalah bil ujrah due to the absence of clear contractual agreement and predetermined compensation, which may lead to elements of uncertainty (gharar). Furthermore, the practice resembles other contracts such as samsarah (brokerage) and ju’alah, thus it can be categorized as a hybrid contract in contemporary Islamic transactions. Therefore, improvements in transparency and clarity of agreement are necessary to align with Islamic economic law principles.